NILAI-NILAI TRI HITA KARANA DALAM PENDIDIKAN TINGGI: BUKTI DARI PERSEPSI DOSEN - Putu Gede Subhaktiyasa (Pascasarjana Universitas Pendidikan Ganesha, 2026)
The integration of cultural values into higher education is receiving increasing attention due to its role in shaping character, social responsibility, and academic culture. The Tri Hita Karana (THK) philosophy is a local value framework that emphasizes harmony in human relationships with God (parahyangan), fellow human beings (pawongan), and the environment (palemahan). However, understanding how internal actors in higher education institutions perceive THK values remains limited. This study aims to analyze lecturers' perceptions regarding the internalization of THK values within the academic culture of higher education institutions. The study employs a descriptive, quantitative design and involves 98 lecturers selected through purposive sampling. Data were collected using a Tri Hita Karana questionnaire covering the dimensions of Parahyangan, Pawongan, and Palemahan. Data analysis was conducted using descriptive statistics. The results indicate that lecturers have a very high perception of the implementation of THK values across all dimensions. The findings indicate that THK has gained legitimacy as a shared value framework within the academic environment and is perceived as part of the organizational culture of higher education institutions. The study reinforces the view that local wisdom not only functions as a cultural symbol but also has the potential to become an indigenous organizational culture that supports the development of values-based higher education. The results contribute to the development of discourse on integrating local wisdom into higher education management and to the strengthening of a more humanistic, harmonious, and sustainable academic culture.